Promoting research in higher education institutions: Literature Review 2016-2021 - Bullón-Solís, Omar (2022)
Research, an essential component in higher education, needs to be promoted due to the low development in educational institutions. The study sought to identify the axes that promote it based on the analysis of articles that addressed the subject. A systematic review was carried out based on the last 5 years, using the Scopus database. Four fundamental axes were identified to promote research, without ensuring that they constitute the only elements for this purpose. Existing literature mentioned the development of research skills, followed by the encouragement of networked collaborations; emphasized the strengthening of the leadership of research centers in university institutions; He referred to the use of information and communication technologies (ICTs) to create and disseminate scientific knowledge. In addition, the promotion of ethics and values in research is also highlighted. It was concluded that these elements should be integrated into the institutional policies of both universities and research-related organizations.